Studies of the permanent incisor eruption and body development of the large East African Zebu (Boran): 2. Relations of incisor eruption with body growth, body development, and carcass composition - Carles, A.B.; Lampkin, K.M. (Cambridge University Press, 1977)
A comparison was made of the growth curves for early and late eruptors (steers whose eruption age of the first incisor pair was less than the mean, and greater than the mean respectively). From birth to 195 weeks early eruptors were consistently heavier than late eruptors (P